RESULTS OF ERIE SILK DYEING FROM FERMENTED BANANA TRUNK BIO-EXTRACTS APPLIED TO THE READY-TO-WEAR FASHION DESIGN - Thanakrit Kaewpilarom; Burin Plengdeesakul; Nirat Soodsang (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The Objectives of the research are 1) To study the variation ratio of color concentration and variation of time duration in bio-extracted, fermented banana trunk dyeing effect to Erie Silk fabric colorfastness and 2) To design and made bio-extracted, fermented banana trunk dyeing Erie Silk fabric into ready-to-wear fashion. The research method was Mixed Methods Research (MMR) which was Experiment and Quantitative Research collecting data from experiments, and employed survey, interview and opinion assessment guidelines to be analysed the colorfastness level according to Thailand Industrial Standard; Average and Deviation, and market acceptances. The results are variation of color concentration and time duration of the bio-extracted, fermented banana trunk to the colorfastness to light, to hot pressing, to dry cleaning, to acid and alkali perspiration, found the colorfastness in the parts: color change and color staining scored was higher more than level 3 in scale of which is acceptable. Exception is the colorfastness to soap wash in all level of concentration and time duration lower than the standard but no effect to color staining to diverse fabric type DW. It is recommended to avoid washing in normal condition. Fashion Application of Erie Silk textile dyed by the bio-extracted, fermented banana trunk found the overall rating at extremely agree at 4.55 in Average, and 0.66 in Deviation.